(untitled) - Warner, Janine (Hoboken, N.J., 2013)
Creating dynamic websites is easy with Dreamweaver CC and this friendly, full-color guide. Updated for the latest version of Adobe's world-renowned web development tool, Dreamweaver CC For Dummies covers all aspects of creating websites, from understanding web design basics to using style sheets, integrating multimedia, implementing responsive design, testing and publishing your sites, and more. With the professional guidance of Web design expert Janine Warner, you'll soon be on your way to building the website you've always wanted.
Keywords: Web sites,Web sites,Dreamweaver (tệp máy tính),Trang web,Trang web,Dreamweaver (Computer file); Authoring programs,Design,Chương trình Authoring,Thiết kế